Analisis Al-Qira’at Al-Sab’ dalam Kitab Tajwid Hilyat Al-Sibyan berdasarkan Tariq Al-Syatibiyyah: Analysis of Al-Qira'at Al-Sab' in the Book of Tajwid Hilyat Al-Sibyan based on Tariq Al-Syatibiyyah - Farnidah, Rifdah; Rizkilah, Nurul; Nurhalisah, Neng Siti; Hanifah, Muti'ah Nur (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2025)
The book Tajwid Hilyat al Sibyan is a work by Shaykh an Nawawi al Bantani (d. 1316 AH), which discusses the rules of Quranic recitation (qiraat). However, some explanations of qiraat in the book do not mention the narrators (rawi) associated with the recitation rules being described. This can lead to confusion for readers who are not well versed in the science of qiraat, especially among the Indonesian public, who generally follow the Hafs recitation according to the tariq of al Syatibiyyah. This research aims to analyze the usuliyyah principles in the book Hilyat al Sibyan based on the tariq al Syatibiyyah, as well as the similarities and differences in the usuliyyah principles found in the book Hilyat al Sibyan according to the tariq al Syatibiyyah. This study employs a qualitative research method, specifically a type of library research. The results of this research show that there are eleven principles which mention differences (ikhtilaf) among the scholars of qiraah. These include Idgam Al Mislain, Ha Damir, Mad Munfasil, Mad Badal, Idgam in the letter zal in the word Idz, Idgam in the letter dal in the word Qad, Idgam in the feminine ta (Ta Tanis), Idgam in the letter lam in the words Hal and Bal, Idgam Mutaqaribain, Idgam Mutajanisain, Mad Muttasil. The similarities lie in the rules of Idgam Al Mislain, Ha Damir, Mad Munfasil, and Mad Badal. The differences are found in the rules of Idgam in the zal in Idz, Idgam in the dal in Qad, Idgam in Ta Tanis, Idgam in the lam in Hal and Bal, Idgam Mutaqaribain, Idgam Mutajanisain, and Mad Muttasil.